Pengaruh Basic Need Satisfaction terhadap Work Engagement pada Pegawai Negeri Sipil Dinas X Kabupaten Bandung - Naura Syifa Salsabila; Agus Budiman (Bandung Conference Series: Psychology Science, 2023)
Abstract. The research was conducted to determine the effect of basic need satisfaction on work engagement at the X Office of Bandung Regency. Basic need satisfaction consists of three basic needs, the need for autonomy, the need for competence, and the need for relatedness, which are individual basic needs as 'nutrition' that must be obtained to maintain development, integrity, and health. (Deci & Ryan, 2000; Gieter, et al., 2017). Work engagement is a positive, satisfying state of mind related to work which is characterized by vigor, absorption, and dedication (Schaufeli, 2002). This study uses a quantitative approach to causality with multiple linear regression analysis techniques. The research subjects were all employees of the Bandung Regency X Office as many as 43 employees. The measuring instrument used in this study is the work-related basic needs satisfaction (W-BNS) from Van den Broeck, et al and the Utrecht Work Engagement Scale (UWES-17) from Schaufeli, et al. The research shows that the majority of employees have a high level of basic need satisfaction and have a high level of work engagement. Multiple linear regretion test results show that basic need satisfaction has an effect on work engagement of 75.3% (R Square .868). All dimensions of basic need satisfaction have influence where the highest influence is on autonomy .477 and the lowest has influence on relatedness .250. Abstrak. Penelitian dilakukan untuk mengetahui pengaruh basic need satisfaction terhadap work engagement pada Dinas X Kabupaten Bandung. Basic need satisfaction terdiri dari tiga kebutuhan dasar yaitu kebutuhan akan otonomi, kebutuhan akan kompetensi, dan kebutuhan akan keterkaitan yang merupakan kebutuhan dasar individu sebagai ‘nutrisi’ yang harus diperoleh untuk mempertahankan perkembangan, integritas, dan kesehatan. (Deci & Ryan, 2000; Gieter, dkk., 2017). Work engagement yaitu sebagai keadaan pikiran yang positif, memuaskan terkait pekerjaan yang ditandai dengan semangat, penyerapan, dan dedikasi (Schaufeli, 2002). penelitian ini menggunakan pendekatan kuantitatif kausalitas dengan teknik analisis linier berganda. Subjek meneliti seluruh pegawai Dinas X Kabupaten Bandung sebanyak 43 pegawai. alat ukur yang digunakan dalam penelitian ini yaitu work-related basic needs satisfaction (W-BNS) dari Van den Broeck, et al dan alat ukur Utrech Work Engagement Scale (UWES-17) dari Schaufeli, et al. Penelitian menghasilkan jumlah pegawai yang memiliki tingkat kepuasan kebutuhan dasar yang tinggi dan memiliki tingkat keterlibatan kerja yang tinggi. Hasil uji linier berganda menunjukkan bahwa kepuasan kebutuhan dasar memberikan pengaruh terhadap work engagement sebesar 75,3% (R Square .868). Seluruh dimensi basic need satisfaction memberikan pengaruh dimana pengaruh tertinggi pada otonomi (autonomy) .477 dan yang memberikan pengaruh terendah pada relatedness (keterkaitan) sebesar .250.